2021
DOI: 10.1001/jamanetworkopen.2021.6303
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Hospital-Based Comprehensive Medication Reviews Including Postdischarge Follow-up on Older Patients’ Use of Health Care

Abstract: IMPORTANCE Suboptimal use of medications is a leading cause of health care-related harm. Medication reviews improve medication use, but evidence of the possible benefit of inpatient medication review for hard clinical outcomes after discharge is scarce. OBJECTIVE To study the effects of hospital-based comprehensive medication reviews (CMRs), including postdischarge follow-up of older patients' use of health care resources, compared with only hospital-based reviews and usual care. DESIGN, SETTING, AND PARTICIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 47 publications
5
50
0
Order By: Relevance
“…Patients were selected from a multicentre, cluster-randomised, crossover trial (MedBridge) conducted between 2017 and 2018 at four Swedish hospitals: the hospitals in Uppsala, Enköping, Västerås and Gävle [ 28 ]. The aim of the trial was to study the effects of pharmacist-initiated hospital-based CMRs, including active follow-up, on older patients’ healthcare utilisation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were selected from a multicentre, cluster-randomised, crossover trial (MedBridge) conducted between 2017 and 2018 at four Swedish hospitals: the hospitals in Uppsala, Enköping, Västerås and Gävle [ 28 ]. The aim of the trial was to study the effects of pharmacist-initiated hospital-based CMRs, including active follow-up, on older patients’ healthcare utilisation.…”
Section: Methodsmentioning
confidence: 99%
“…A total number of 2637 patients were included. The incidence of unplanned hospital revisits within 12 months did not differ between the intervention groups and the control group [ 28 ]. A process evaluation of the trial [ 29 ] showed that in less than half of the intervention patients (46%), the CMR included a medication reconciliation at discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the follow-up has gained increased attention over the last decade. In Sweden, the Medbridge trial [ 21 ] investigated the effects of hospital-based comprehensive medication reviews where one arm included post-discharge follow-ups, but found no effect on patients’ unplanned hospital visits within 12 months when compared to a control group. In contrast, a Danish study of a similar intervention explicitly used the patient-centred technique of motivational interviewing in their follow-up; they found that readmissions within 30 and 180 days were decreased among patients who received medication reviews and follow-up [ 22 ].…”
Section: Commentarymentioning
confidence: 99%
“…Recent trials on the effectiveness of pharmacy-led TOC initiatives have used a variety of pharmacy-led intervention components with mixed results. The Medication Reviews Bridging Healthcare (MedBridge) trial conducted by Kempen et al [ 15 ] evaluated the effect of two distinct pharmacist-led interventions, a comprehensive medication review (CMR) and CMR with detailed and structured post discharge follow-up, on the primary endpoint of emergency department attendances and admissions. The results of the MedBridge trial failed to show a significant difference between standard care and intervention groups.…”
Section: Introductionmentioning
confidence: 99%